Women’s Agency in the Practice of Ampa Sabae: An Analysis of Islamic Law and Social Reality in Bima - Ade Irmah Imamah; Syarifah; Amrin; Asfari (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to analyze the practice of ampa sabae in the Mbojo Bima community from the perspectives of Islamic law and social reality, with a particular emphasis on women’s agency as the primary actors in responding to social issues such as premarital pregnancy and male irresponsibility. Theoretical framework: This study is grounded in socio-legal theory, Islamic legal theory, and agency theory, emphasizing the interaction between custom, sharia, and social realities, as well as the framework of maqāṣid al-sharīʿah, particularly ḥifẓ al-nasl (protection of lineage). Literature review: This study reviews key discussions on Islamic marriage law, women’s agency in socio-religious contexts, the relationship between ʿurf (custom) and Islamic law, the concept of fiqh al-ḍarūrah, and the role of local practices in shaping Islamic legal implementation. Method: This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving perpetrators, community leaders, and religious leaders in Bima Regency. Data analysis was conducted through data reduction, data presentation, and inductive conclusion drawing. Results: The findings reveal that the practice of ampa sabae is a multidimensional phenomenon reflecting the dialectic between custom, sharia, and social reality. From an agency perspective, women are positioned as active actors who initiate marriage, determine partners, and demand responsibility from men. From an Islamic legal perspective, this practice is ambivalent: normatively inconsistent with ideal marriage procedures, yet it can be understood within the framework of fiqh al-ḍarūrah and public interest (maṣlaḥah) as an effort to preserve lineage (ḥifẓ al-nasl). Implications: This study highlights the need for a contextual and responsive approach to Islamic law and emphasizes the importance of the role of ulama and policymakers in ensuring that local practices align with principles of justice, consent, and public interest. Novelty: This study offers a comprehensive analysis through the integration of women’s agency perspectives with a socio-legal and maqāṣid al-sharīʿah approach, positioning women as active subjects in local religious practices.